Learning Reflection During Covid-19 Pandemic: Teacher Perception Toward Google Form Based Test - Zakwandi, Rizki; Wulansari, Putri; Maula, Atika Rofiqatul; Hasan, Suhandi; Anditya, Novia (Yayasan Nurul Yakin Bunga Tanjung, 2022)
This study aims to analyze the usability of Google Form as an online learning assessment tool. This study uses a quantitative approach through survey methods. Respondents in this study were teachers from various levels of education ranging from elementary to high school levels and from various subjects. The respondents' answers were collected by using a Google Form questionnaire. The analysis results show that using Google Forms is the most straightforward alternative for conducting online assessments. Assessment through Google Form has the principle of being an open system, so it takes the ability to use it. The novelty in this study is to determine the proficiency of Google Forms as an assessment tool during the COVID-19 pandemic and teacher perceptions of the assessment principles using Google Forms. Using Google Forms as an assessment tool during the Pandemic requires additional teachers' competencies for designing a better assessment process. Thus, the comparison of the assessment principle with the assessment process using Google Form to conduct a Pedagogical Review can be considered in designing an assessment using Google Form.